Gender roles and relations in terrorist organizations in Africa: a radical feminist comparative study of Boko Haram and al Shabaab - Forster, Courtney Paige (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.